2020
DOI: 10.1002/ange.202001701
|View full text |Cite
|
Sign up to set email alerts
|

Photo–thermo Catalytic Oxidation over a TiO2‐WO3‐Supported Platinum Catalyst

Abstract: Photo–thermo catalysis, which integrates photocatalysis on semiconductors with thermocatalysis on supported nonplasmonic metals, has emerged as an attractive approach to improve catalytic performance. However, an understanding of the mechanisms in operation is missing from both the thermo‐ and photocatalytic perspectives. Deep insights into photo–thermo catalysis are achieved via the catalytic oxidation of propane (C3H8) over a Pt/TiO2‐WO3 catalyst that severely suffers from oxygen poisoning at high O2/C3H8 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…The obvious photoresponsive phenomenon for NO production proved that the reaction was driven by photon illumination (Figure 2c). 31 With the increase of temperature from 25 °C to 150 °C (Figure S9), an obvious decay of photoluminescence intensity was observed in Ru SAs/TiO 2 , indicating the reduced electron-hole recombination at higher temperature. Moreover, the NO-TPD profile (Figure S10) showed that NO on Ru SAs/TiO 2 desorbed at 110 and 246 °C.…”
Section: Resultsmentioning
confidence: 95%
“…The obvious photoresponsive phenomenon for NO production proved that the reaction was driven by photon illumination (Figure 2c). 31 With the increase of temperature from 25 °C to 150 °C (Figure S9), an obvious decay of photoluminescence intensity was observed in Ru SAs/TiO 2 , indicating the reduced electron-hole recombination at higher temperature. Moreover, the NO-TPD profile (Figure S10) showed that NO on Ru SAs/TiO 2 desorbed at 110 and 246 °C.…”
Section: Resultsmentioning
confidence: 95%
“…Although here it is viewed in a specific context and illustrated by examples based on the advantageous coupling of renewable solar (hydrogen) and biomass (oxygenates, CO2) resources, the new phenomenology is clearly fundamental in origin and provides the basis of a new paradigm in applied catalysis. From a broader perspective, equally impressive reports from applications in other fields, e.g., environmental chemistry [205,206], fuel combustion [207], syngas production [208] or coupled solar PV/hydrogen generation [209], have appeared even during the drafting of this review.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, electron spin resonance spectroscopy is an appropriate approach to explore the evolution of these transient oxygen species, due to its extreme sensitivity to paramagnetic features. 142,143 At a steady state, the type and chemical state of oxygen species under reaction conditions can be elucidated by performing AP-XPS measurements of the O 1s feature. To gain a deeper understanding of the variations in oxygen reactivity due to electronic, geometric, and kinetic modifications at a specific orbital level, the total density of state (DOS) is usually calculated and projected to the surface atoms of interest (e.g., O and neighboring metals) using DFT calculations.…”
Section: How Do Obtain Structural and Mechanistic Insights Into Bimet...mentioning
confidence: 99%